PENGARUH PERSAINGAN PASAR PRODUK DAN TATA KELOLA PERUSAHAAN TERHADAP KINERJA PERUSAHAAN YANG DIMODERASI OLEH KEPEMILIKAN SAHAM PEMERINTAH - Ilham Budi Hutomo Adji; Rr. Karlina Aprilia Kusumadewi (Diponegoro Journal of Accounting, 2023)
The purpose of this study is to examine the relationship of product market competition and corporate governance on firm performance with the impact of the presence of state ownership. The dependent variable that used in this study is firm performance. Product market competition (PMC) and corporate governance used as independent variable. Furthermore, this study used state ownership as a moderating variable.The sample in this study consists of 132 banking companies that listed on Indonesia Stock Exchange in the period 2017-2019. The data that used in this study was secondary data and selected by using purposive sampling method. The technique of analysis used for examining the hypothesis was multiple regression analysis.Based on the empirical results of this study show that product market competition (PMC) has negative influence on firm performance. This study also show that corporate governance has positive impact on firm performance. Lastly, this study found that product market competition (PMC) has positive influence towards firm performance moderated by state ownership.